2022
DOI: 10.3390/land11081202
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital in Neighbourhood Renewal: A Holistic and State of the Art Literature Review

Abstract: In the new era of sustainable urban development, neighbourhood renewal has received increasing attention. Social capital, which can be defined as the value embedded in the relationship between residents, plays a significant role in the process of neighbourhood renewal. However, within the current neighbourhood renewal knowledge domain, there is a lack of clear and systematic understanding of the various components that make up social capital, how they are formed, and how they impact neighbourhood renewal. With… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 139 publications
(174 reference statements)
0
9
0
Order By: Relevance
“…SSC develops social structures and facilitates information sharing and cooperation through actors and relationships under defined rules and procedures (Alan and Köker, 2021). Information exchange is the core component of SSC (Lawson et al, 2008;Yim and Leem, 2013;Li et al, 2022). García-Villaverde et al (2017) suggested that SSC emphasizes the control of information in the social system structure.…”
Section: Structural Social Capital In Neighborhood Renewalmentioning
confidence: 99%
See 1 more Smart Citation
“…SSC develops social structures and facilitates information sharing and cooperation through actors and relationships under defined rules and procedures (Alan and Köker, 2021). Information exchange is the core component of SSC (Lawson et al, 2008;Yim and Leem, 2013;Li et al, 2022). García-Villaverde et al (2017) suggested that SSC emphasizes the control of information in the social system structure.…”
Section: Structural Social Capital In Neighborhood Renewalmentioning
confidence: 99%
“…First, this study suggested that the effect of multi-level social capital in neighborhood renewal should be examined in future research. As proposed by Li et al (2022) social capital can be classified into resident level and neighborhood level. In this study, the limitation of the data structure did not allow for a multi-level analysis at resident-level and neighborhood-level.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Zhang, Zhang, & Guo, 2021), cumulative prospect theory (Ebrahimigharehbaghi, Qian, de Vries, & Visscher, 2022), and other relevant theories (Guo, Li, & Wang, 2018;Liang, Tao, Hong, & Shen, 2019). Among the various theoretical frameworks applied to the study of resident behavior, the theory of planned behavior is one of the most commonly used (Jin, Li, Jansen, Boumeester, & Boelhouwer, 2022;Li, Huang, Liu, Shrestha, & Xinyue, 2022). This theory hypothesizes that behavior is determined by three key factors: attitude, subjective norms, and perceived behavioral control (Bosnjak, Ajzen, & Schmidt, 2020).…”
Section: The Theoretical Framework Of Residents' Cooperative Behavior...mentioning
confidence: 99%
“…Collective social capital refers to shared social networks, norms, and values that exist within a group or community that can lead to cooperative behavior, collective action, and mutual benefits (Svendsen & Svendsen, 2009). According to Li, Huang, et al (2022), collective social capital includes general trust, social norms, and system control, and collective social capital promotes the emergence of individual social capital. In this study, individual and collective social capital are defined as follows:…”
Section: The Theoretical Framework Of Residents' Cooperative Behavior...mentioning
confidence: 99%
“…Research (Gannon and Roberts 2018;Li et al 2022) indicates that reinforcement Social capital is one of the strategies to get out of moments of inertia. The social capital that is the material object of this study is Civil Society in the form of community-based educational institutions (Rasdi 2020;Hafenbrack et al 2019).…”
Section: Introductionmentioning
confidence: 99%